Online Learning Resource Management in CPNS Basic Training - Rina Widiasih (Jurnal Prajaiswara, 2020)
The health and safety of CPNS training participants, Widyaiswara, families, and communities is a top priority in setting learning policies. Latsar CPNS is one of the training that feel the impact of the pandemic. In this COVID-19 emergency, procedurally, by Plan No. 12 of 2018 and Circular No. 10/K.1/Hkm.02.3/2020 concerning Technical Guidelines for the Implementation of Training During the Coronavirus Disease (Covid-19) Pandemic, participants Latsar CPNS and related parties began to change the learning strategy which was originally face-to-face to online learning. The entire implementation of the CPNS latsar in Indonesia was impacted by the pandemic by holding online learning methods. This study describes the implementation of online learning during the pandemic. This research is a literature review research with the dynamic search method of learning resources conducted online. Data collection includes documents, articles, or news related to learning resources used during COVID-19 online learning. Furthermore, the collected data is analyzed for description. Online learning resources used during the CPNS Latsar training are using WhatsApp (WA), Google Forms, Google Classroom, Google Drive, Youtube, WA groups, and even face-to-face with the Zoom Meeting application. The purpose of this research is to get input and improvements for better online learning resources.